2021
DOI: 10.1016/j.ejro.2021.100383
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomical analysis of inflammation in hand psoriatic arthritis by Dual-Energy CT Iodine Map

Abstract: This study aimed to identify the detailed location of inflammatory lesions and its frequency of hand PsA on DECT Iodine Map with referring the cadaveric specimen. Materials and methods: Thirty-eight anatomical landmarks were selected as a potential inflammatory sites in the thumb and middle finger. We included 22 symptomatic PsA patients who underwent contrast enhanced DECT of the hand. MR images and macroscopic specimens of thumb and middle finger were prepared from a cadaver. Two musculoskeletal radiologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the study of Fukuda et al, the potential of DECT iodine maps was shown in regard to the detection of synovitis in patients with psoriatic arthritis [ 7 , 11 ]. In a further study by this group, DECT iodine maps were also successfully used in therapy monitoring [ 24 ] and in the anatomical analysis of psoriatic arthritis [ 25 ]. Nonetheless, a recent study found no advantage of DECT over CT-S for synovitis detection [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Fukuda et al, the potential of DECT iodine maps was shown in regard to the detection of synovitis in patients with psoriatic arthritis [ 7 , 11 ]. In a further study by this group, DECT iodine maps were also successfully used in therapy monitoring [ 24 ] and in the anatomical analysis of psoriatic arthritis [ 25 ]. Nonetheless, a recent study found no advantage of DECT over CT-S for synovitis detection [ 12 ].…”
Section: Discussionmentioning
confidence: 99%